Multibody Dynamic Analysis of a Wind Turbine Drivetrain in Consideration of the Shaft Bending Effect and a Variable Gear Mesh Including Eccentricity and Nacelle Movement - Park, Yonghui; Park, Hyunchul; Ma, Zhe; You, Jikun; Shi, Wei (Frontiers in Energy Research, 2021)
Due to the energy crisis and global warming issues, the wind energy is becoming one of the most attractive renewable energy resources in the world. The drivetrains in the wind turbine tend to fail more prematurely than those in any other applications. Gearbox is the subsystem that causes the most downtime for the wind turbines. In the previous research, only the torsional flexibility of the shaft was considered in the drivetrain model. However, because the shaft is longer than other parts, and components connected by the shaft affect each other via shaft bending, the flexibility of the shaft cannot be ignored. In this study, a spherical joint that consists of three rotational springs was used to define the shaft bending. This shaft bending will affect the drivetrain rotation, the translational motion and the gear mesh contact force. Additionally, the eccentricity and the nacelle movement are analyzed due to the coupled motion. In this paper, a mathematical model of the drivetrain is proposed, which is a three-dimensional dynamic model that includes flexible bearings, a gear mesh model, shaft flexibility, eccentricity, and nacelle movement. The equation of motion of the drivetrain is derived using Lagrange’s equation. The governing equation is solved numerically via direct numerical integration. The dynamic responses of the system and contact forces between the gear tooth in the time and frequency domains are calculated numerically. The study shows that this dynamic model of the drivetrain will be highly useful for subsequent studies on the wind turbine condition monitoring.